Neutrophil depletion for early allogeneic islet survival in a methacrylic acid (MAA) copolymer-induced, vascularized subcutaneous space - Won, So-Yoon; Kinney, Sean M.; Sefton, Michael V. (Frontiers in Transplantation, 2023)
Islet transplantation is a promising treatment for type I diabetes (T1D). Despite the high loss of islets during transplantation, current islet transplant protocols continue to rely on portal vein infusion and intrahepatic engraftment. Because of the risk of portal vein thrombosis and the loss of islets to instant blood mediated inflammatory reaction (IBMIR), other transplantation sites like the subcutaneous space have been pursued for its large transplant volume, accessibility, and amenability for retrieval. To overcome the minimal vasculature of the subcutaneous space, prevascularization approaches or vascularizing biomaterials have been used to subcutaneously deliver islets into diabetic mice to return them to normoglycemia. Previous vascularization methods have relied on a 4 to 6 week prevascularization timeframe. Here we show that a vascularizing MAA-coated silicone tube can generate sufficient vasculature in 2 to 3 weeks to support a therapeutic dose of islets in mice. In order to fully harness the potential of this prevascularized site, we characterize the unique, subcutaneous immune response to allogeneic islets in the first 7 days following transplantation, a critical stage in successful engraftment. We identify neutrophils as a specific cellular target, a previously overlooked cell in the context of subcutaneous allogeneic islet transplantation. By perioperatively depleting neutrophils, we show that neutrophils are a key, innate immune cell target for successful early engraftment of allogeneic islets in a prevascularized subcutaneous site.